As ocupações das escolas públicas do Paraná em 2016 e as teorias críticas da educação - Luz, Simão Diego Zanchetti da (2020)
The present study aims to investigate the occupancies in the state schools in 2016. Initiated as a reaction to the acts imposed by the federal government, they guided the political discussions in the most different social spaces. Occupancies were a phenomenon of great impact in the struggles for the public school, not only because of the reach that this movement had, but also because it was a tactic of struggle different from the traditional manifestations of social movements. We researched the occupancies and their historical situation, the tactics used, the internal dynamics, the favorable and oppositional speeches and the results of the students' action. In the first chapter, we present a study on the main critical theories of education to understand the relationship between education and society, identify possible limits in theories and justify our theoretical positioning. And so, the discussion and analysis in the sequence of the work is guided by the concept of society of dialectical historical materialism, and the understanding of education contained in the “historical-critical pedagogy”.